SYNTHESIS OF MAGNETITE-MODIFIED NATURAL ZEOLITE USING COPRECIPITATION AND PHYSICAL MIXING TECHNIQUES - Teguh Pambudi; Hilman Imadul Umam (Indonesian Journal of Pure and Applied Chemistry, 2023)
The synthesis of magnetite-modified natural zeolite has been carried out using two techniques, namely coprecipitation and physical mixing. The characteristics (crystallinity, pore characteristics, and recovery capabilities) of the resulting composites are compared. In addition, the effect of the Fe3O4 fraction (25.0% w/w, 33.3% w/w, and 50.0% w/w) on the composite characteristics was also evaluated. The results showed that the natural zeolite/Fe3O4 prepared using the coprecipitation technique showed better distribution of Fe3O4 than the physical mixing technique. It was observed that the natural zeolite's XRD peak intensity decreased as the Fe3O4 content increased. In accordance with the N2 adsorption-desorption isotherm, the pore spaces of the natural zeolite have been found to be filled by suspended Fe3O4 particles. Therefore, both natural zeolite/Fe3O4 prepared by coprecipitation and physical mixing had smaller pore diameters than washed natural zeolite. Then, in terms of recovery ability, natural zeolite/Fe3O4 prepared using the coprecipitation technique has greater recovery ability than natural zeolite/Fe3O4 prepared by physical mixing, with an increase in the Fe3O4 percentage typically enhancing the composite's recovery ability.